Come leggere il DeuteroIsaia - Cortese, Enzo (Liber Annuus, 2008)
Abstract The author emphasizes the fact that the true characteristic of the monotheistic God of DtIs is that He is perceived as the God of all peoples and not only of Israel. The privileges of Israel including the monarchic-messianic one, must be re-evaluated from a new point of view, that no longer excludes non-Jews from salvation. Only from this universal viewpoint, is it possible to understand how a non-Jew, Cyrus, could have been chosen by God as an instrument of salvation, without removing the key position from Israel. The four poems of the Lord’s Servant were originally independent. This was not only because of critical-literary reasons, but also based on the content, for example where the Servant is not Israel but rather the Redeemer of Israel, as can be clearly seen in the fourth poem and also in the second one (in 49,5). The first two are clearly opposed to Cyrus and they are inserted just before the passages that refer to him. They indicate that now the true Mediator of salvation is not the Persian Emperor but rather the Messiah. The last poem describes the fruit of the messianic suffering, until death and burial. Its insertion at the end of the entire book is a wonderful solution to the problems, anxieties and hopes of the book that becomes the key and the conclusion of the entire message of DtIs.